Muscarinic acetylcholine receptor 3 mediates vagus nerve-induced gastric cancer. (November 2018) - Wang, Linjun; Xu, Jianghao; Xia, Yiwen; Yin, Kai; Li, Zheng; Li, Bowen; Wang, Weizhi; Xu, Hao; Yang, Li; Xu, Zekuan
Abstract Increasing evidence shows that the vagus nerve plays an important role in tumourigenesis. However, the effects and underlying mechanisms of the vagus nerve on gastric cancer (GC) development have not been established. In this study, we performed a unilateral truncal vagotomy at the subdiaphragmatic level in a mouse xenograft GC model to study the effects of the vagus nerve on GC development. Gene microarray analysis was used to explore the mechanism underlying this process. Significantly altered genes and pathways were analysed by Kyoto Encyclopaedia of Genes and Genomes analysis tool. We also detected muscarinic acetylcholine receptor 3 (M3) mRNA and protein levels by quantitative real-time polymerase chain reaction and immunohistochemical staining in mouse stomach tissue. To further confirm the functional role of M3, an in vivo M3 selective antagonist (darifenacin) assay was applied. Finally, we determined the M3 protein levels in human GC tissues and paired non-cancerous gastric tissues by immunohistochemical staining. We found that the surgical vagotomy inhibited the development of GC in an orthotopic xenograft mouse model. Further analysis showed that multiple signalling pathways participated in this process and that M3 was a key factor in these pathways. We established that the M3 mRNA and protein levels decreased in the vagotomy group relative to the sham group. We also demonstrated that the M3 antagonist suppressed the development of GC. Finally, we revealed that M3 protein level was up-regulated in human GC tissues. In conclusions, we revealed the functional role of M3 on mediating the effects of the vagus nerve on GC. Our study contributes to understanding the mechanism underlying the interaction between GC and the vagus nerve and may help to identify new therapeutic targets for GC.